Prevalence and risk factors of burnout among community pharmacists in the Aseer region, Saudi Arabia: a cross-sectional study - Khobrani, Moteb; Alshahrani, Sultan M. (Frontiers in Pharmacology, 2026)
BackgroundBurnout incidents among community pharmacists continue to increase globally, resulting in impaired job performance and patient care as well as mental health deterioration. Research studies on pharmacist burnout and its connected risk factors remain insufficient for Saudi Arabian pharmacists.ObjectivesThis research aimed to investigate burnout frequency alongside related risk elements for Saudi Arabian community pharmacists in the Aseer region of Saudi Arabia.Materials and MethodsA cross-sectional survey was conducted among community pharmacists in the Aseer region of Saudi Arabia between March and July 2025. A structured questionnaire collected data on demographics, occupational factors, and burnout using the Maslach Burnout Inventory–Human Services Survey (MBI-HSS). Statistical analyses were performed using SPSS (version 25.0), applying chi-square tests, t-tests, Pearson correlations, and logistic regression at a significance level of p < 0.05.ResultThe analysis revealed widespread burnout symptoms among study participants, including emotional exhaustion in 78.2% of respondents. In comparison, depersonalization affected 65.4% of participants, and a decline in personal accomplishment was experienced by 72.6%. Overall, a high proportion of participants demonstrated moderate-to-high burnout based on MBI-HSS cutoffs. Significant positive correlations were observed between burnout and heavy workload (p = 0.002), extended working hours (p = 0.004), and insufficient financial compensation (p = 0.006). Female pharmacists showed higher emotional exhaustion scores than their male counterparts, with 29.8 ± 6.4 and 25.6 ± 5.9, respectively (p = 0.03). Pharmacists who exceeded 48 h per week showed higher levels of professional burnout (p = 0.01), while those younger than 35 years demonstrated increased emotional exhaustion compared to their older counterparts (p = 0.02).ConclusionThe findings indicate a high prevalence of burnout among community pharmacists in the Aseer region of Saudi Arabia, influenced by workload, long working hours, insufficient compensation, and demographic factors. Implementation of workload management systems, mental health support, and career development resources is recommended to decrease burnout and enhance pharmacist well‐being and patient care quality.